Six-membered ring systems: with O and/or S atoms - Santos, Clementina M.M. (2021)
A large variety of publications have emerged in 2020 involving O- and S-six-membered ring systems. Special emphasis is given to the large number of reviews that have been published during this year, perhaps because the pandemic situation caused by COVID-19 forced scientists around the world to leave their work in the laboratory and concentrate their efforts on the compilation of reviews. Hereinafter, we provide a personal overview of the most important develop